2017
DOI: 10.1039/c7sm00487g
|View full text |Cite
|
Sign up to set email alerts
|

Micro- and nano-patterned elastin-like polypeptide hydrogels for stem cell culture

Abstract: We show that submicron-sized patterns can be imprinted into soft, recombinant-engineered protein hydrogels (here elastin-like proteins, ELP) by transferring wavy patterns from polydimethylsiloxane (PDMS) molds. The high-precision topographical tunability of the relatively stiff PDMS is translated to a bio-responsive, soft material, enabling topographical cell response studies at elastic moduli matching those of tissues. Aligned and unaligned wavy patterns with mold periodicities of 0.24–4.54 µm were imprinted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 62 publications
0
13
0
Order By: Relevance
“…Robert et al showed that hydrogels with 1.9 μ m of grooves by casting method were effective in inducing cell alignment, but cells aligned poorly on grooves with depth less than 1 μ m. 163 Adipose-derived stem cells were also shown to exhibit alignment when the topography width is larger than 0.60 μ m and height larger than 170 ± 100 nm on elastin-based hydrogel. 164 Fibroblasts were cultured on PAM hydrogels with 5 μ m wide and 1 μ m high lines with stiffness of 13, 37, and 145 kPa. Cell elongation was induced by topography on all substrates.…”
Section: Surface Topography Affect Cell Responses On Hydrogelmentioning
confidence: 99%
“…Robert et al showed that hydrogels with 1.9 μ m of grooves by casting method were effective in inducing cell alignment, but cells aligned poorly on grooves with depth less than 1 μ m. 163 Adipose-derived stem cells were also shown to exhibit alignment when the topography width is larger than 0.60 μ m and height larger than 170 ± 100 nm on elastin-based hydrogel. 164 Fibroblasts were cultured on PAM hydrogels with 5 μ m wide and 1 μ m high lines with stiffness of 13, 37, and 145 kPa. Cell elongation was induced by topography on all substrates.…”
Section: Surface Topography Affect Cell Responses On Hydrogelmentioning
confidence: 99%
“…Although hydrogels can be fabricated from synthetic and natural polymers, synthetic polymers have become more relevant due to their long service life, high mechanical strength, and higher water absorption [ 102 ]. Relevant hydrogel materials used to culture stem cells include PEG [ 103 ], poly(2-hydroxyethyl methacrylate) (HEMA) [ 104 ] elastin [ 105 ], collagen [ 106 ], and hyaluronic acid [ 107 ].…”
Section: Mimicking the Spatial And Physical Components Of The Stem Cell Microenvironmentmentioning
confidence: 99%
“…[38][39] Patterned topographies with a size range from sub-micrometers to tens of micrometers directly alter cell morphology along the patterns and differentiate stem cells by impact on their alignment and orientation. [40] Nanometer-sized patterns with the dimensions of integrins induce nano-scale integrin clustering, and assembly of focal adhesion proteins such as paxillin, vinculin, and focal adhesion kinase (FAK) in stem cells, which induce cytoskeleton reorganization and alter cytoskeletal tension (Figure 2). [41][42] The mechanical tension activated by specific topographies actuates integrin-mediated intracellular signaling and mechanotransduction pathways via nuclear reorganization and eventually rearranges the centromere through deformation of the nucleus.…”
Section: Stem Cells and Neural Differentiationmentioning
confidence: 99%